2021
DOI: 10.1002/suco.202100076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aggregate packing optimization and cement paste volume on the properties of natural and recycled aggregate concrete

Abstract: This paper investigates the influence of aggregate packing optimization based on a particle packing method (PPM) and cement paste volume (CPV) on the workability and mechanical properties of both natural aggregate concrete (NAC) and recycled aggregate concrete (RAC). The slump, compressive strength, flexural strength and Young's modulus of concrete were first examined, followed with the characterization of macro-pore structure inside RAC by using X-ray computed tomography (CT). The results indicate that the PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…However, it is more glaring that there is a lack of information and recommendations for reducing the standard modulus values when using granite aggregate. It is clear from own research, as well as from the examples cited domestically [5,10,11,12] and abroad [7,8], that the deformability of concrete with granite aggregate is significant, and the values of modulus of elasticity given in the standard are greater than the actual ones, which was confirmed by the tests results. It seems that this should be taken into account in the form of a national annex to the standard, while it is advisable to conduct more extensive studies in advance on the most commonly exploited Polish granite deposits.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…However, it is more glaring that there is a lack of information and recommendations for reducing the standard modulus values when using granite aggregate. It is clear from own research, as well as from the examples cited domestically [5,10,11,12] and abroad [7,8], that the deformability of concrete with granite aggregate is significant, and the values of modulus of elasticity given in the standard are greater than the actual ones, which was confirmed by the tests results. It seems that this should be taken into account in the form of a national annex to the standard, while it is advisable to conduct more extensive studies in advance on the most commonly exploited Polish granite deposits.…”
Section: Resultssupporting
confidence: 56%
“…1. Eff ect of aggregate type on the elasticity modulus of concrete according to Alexander [7] basalt aggregate, lower value by about 10% was obtained with diabase, dolomite and limestone aggregate, and even lower (by about 20%) with granite and porphyry aggregate [5]. On the other hand, Deja [6], referring to the results of foreign studies of the ultimate deformability of concrete depending on the mineral composition of the aggregate (granite, porphyry, diabase, basalt, limestone, quartz, gravel) in 1972, reported that at the highest tensile strength of concrete with limestone aggregate has the lowest elongation.…”
Section: Effect Of the Coarse Aggregate Type On The Modulus Of Elasti...mentioning
confidence: 92%
See 1 more Smart Citation
“…Especially, the angular and rough textured particles when they are bound with cement paste create a better interlocking behavior. This enhances a better bonding characteristic once cement is hydrated and enable a good resistance to compression 68 . These characteristics of concrete are reduced when it incorporates round shape and smooth textured particles due to the lower bonding characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…This enhances a better bonding characteristic once cement is hydrated and enable a good resistance to compression. 68 These characteristics of concrete are reduced when it incorporates round shape and smooth textured particles due to the lower bonding characteristics.…”
Section: Compressive Strengthmentioning
confidence: 99%